A LEXICAL COHESION ANALYSIS ON OSCAR WILDE’S SHORT STORY THE SELFISH GIANT - Raudhatul Islam (IAI Al-Qolam, 2022)
This article aims to discuss what lexical cohesive devices are applied to a short story The selfish Giant written y Oscar Wilde. Since the data of this article have been collected by reading some books in the library, it is called the library research. Since the data in this article are lexical cohesive devices found in the short story The Selfish Giant, they are called qualitative data. This article uses descriptive method to analyze the data. Through the analysis and the discussion, it is found that there are many lexical items in the short story The Selfish Giant that can be categorized as lexical cohesive devices. The lexical cohesive devices establish the cohesion and coherence in the short story. Repetition plays an important role in making the text coherent and unified. That is why the lexical cohesive device of repetition is frequently used in The Selfish Giant. This repetition creates the relation of meaning in the clauses, so it can build continuity in the text. The continuity that is demonstrated by the repetition shows that there is cohesion in the text. The synonym is the second type of reiteration that is found in The Selfish Giant. The use of the synonym shows two lexical items or more that are similar in meaning. The use of synonym in the text is very helpful to build cohesion because synonym holds the sentences together and gives cohesive effect to the text. The application of lexical cohesive devices makes the text coherent and unified because it links the sentences and helps the readers understand the text. Moreover, the analysis shows that the lexical cohesive device that is most often used to relate sentences in The Selfish Giant is repetition. Therefore, the repetition is claimed as the simplest way of connecting sentences, and of course the repetition plays an important role in making the text coherent and unified. Keywords : Discourse Analysis, Short Story, Lexical Cohesion.